Macroeconomic effects of the anticipation and implementation of tax changes in Germany: Evidence from a narrative account - Désirée I. Christofzik; Angela Fuest; Robin Jessen (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
This paper quantifies the dynamic macroeconomic effects of tax changes in Germany, allowing for anticipation effects of preannounced tax reforms. Identification is achieved using a narrative approach which provides information about the timing of tax reforms. For an anticipated tax shock, we find an implied peak tax multiplier after implementation of 1.7. However, this positive effect is accompanied by significantly negative anticipation effects, in particular for output, investment, and hours worked. A substantial positive impact is observed only several quarters after implementation. Our results suggest that tax policy may thus be able to exploit anticipation effects by strategically announcing policy measures. – – Diese Studie quantifiziert die makroökonomischen Effekte von Steuerrechtsänderungen in Deutschland und berücksichtigt dabei mögliche Antizipationseffekte. Diese können sich bereits mit der Ankündigung einer Reform zeigen. Die Steuerschocks werden über einen narrativen Ansatz identifiziert, der Informationen über den zeitlichen Ablauf der Gesetzgebungsverfahren liefert. Eine antizipierte Steuersenkung entfaltet ihren maximalen Effekt auf das Bruttoinlandsprodukt erst mehr als zwei Jahre nach ihrer Umsetzung. Der Steuermultiplikator beträgt dann 1,7. Dieser positive Effekt wird jedoch von erheblichen negativen Antizipationseffekten begleitet. Dies gilt insbesondere für das Bruttoinlandsprodukt, die Investitionen und die Arbeitsstunden. Ein bedeutsamer positiver Effekt lässt sich hier erst mehrere Quartale nach der Umsetzung der Reform beobachten. Die Ergebnisse dieser Studie deuten daher darauf hin, dass sich die Steuerpolitik prinzipiell Antizipationseffekte zunutze machen kann, um die Konjunktur zu stabilisieren.
Keywords: H20; H30; E32; E62; 330; fiscal policy; tax policy; anticipation effects